2011
DOI: 10.1186/1471-2458-11-419
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of point of care HIV testing in community outreach and GUM drop-in services in the North West of England: A programmatic evaluation

Abstract: BackgroundIn Liverpool, injecting drug users (IDUs), men-who-have-sex-with-men (MSM) and UK Africans experience a disproportionate burden of HIV, yet services do not reach out to these groups and late presentations continue. We set out to: increase testing uptake in targeted marginalized groups through a community and genitourinary medicine (GUM)-based point of care testing (POCT) programme; and conduct a process evaluation to examine service provider inputs and document service user perceptions of the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 23 publications
(17 reference statements)
1
42
0
4
Order By: Relevance
“…New HIV and syphilis cases were then diagnosed and linked to treatment and care. The same was found by MacPherson et al [54] in injecting-drug users (IDUs), MSM, and UK Africans, who successfully reached these target groups, many of whom would not have been tested otherwise. Studies performed in Bangalore, India, and the Amazon region of Brazil [22,44,55,56] showed that POCT was helpful in alleviating the impact of syphilis in both pregnant and non-pregnant outreach populations, including high-risk individuals such as sex workers.…”
Section: Impact Of Tests' Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…New HIV and syphilis cases were then diagnosed and linked to treatment and care. The same was found by MacPherson et al [54] in injecting-drug users (IDUs), MSM, and UK Africans, who successfully reached these target groups, many of whom would not have been tested otherwise. Studies performed in Bangalore, India, and the Amazon region of Brazil [22,44,55,56] showed that POCT was helpful in alleviating the impact of syphilis in both pregnant and non-pregnant outreach populations, including high-risk individuals such as sex workers.…”
Section: Impact Of Tests' Introductionsupporting
confidence: 58%
“…Lately, it seems that this may be overcome with the availability of treponemal and non-treponemal POC tests that may be used successfully in areas with unfavourable conditions for a normal diagnostic laboratory. Overall, these tests have shown to have good sensitivities and specificities [30,32,33,47] and to increase screening in different population groups from pregnant women to sex workers, MSM and drug addicts, and other outreach populations anywhere in the world [22,25,44,[54][55][56]. The tests are generally well received by local health care workers and clients in places where studies have been performed [24,25,40,49,56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive peer counselling also increased the uptake of testing (22). Alternative community venues (200) are used for on-site testing including gay saunas (201), event-related outreach (40), and college-based testing (202). Offering other tests (eg for STIs, alcohol or drug use) along with HIV testing may increase uptake in some groups of MSM (203).…”
Section: Motivation For and Barriers To Hiv Testingmentioning
confidence: 99%
“…In contrast, RHT involves finger-prick blood or oral fluid specimen collection with results provided during the same visit, which may make testing more convenient. Barriers to implementing RHT reported among service providers include: lack of time [12,13]; lack of confidence in their own competency and skills and fear of delivering positive results [14,15]; concern regarding reliability and false positive results [16,17]; and perceiving RHT as too difficult for nonexperts [18].Although many studies have assessed acceptability of RHT in a variety of settings and patient groups, and among providers at various stages of implementation [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], few studies have assessed differences in acceptability between professions [29,30]. To our knowledge, no published studies have examined if the number of tests performed and experience of false test results impact on provider acceptability.…”
mentioning
confidence: 99%